2019
DOI: 10.1097/scs.0000000000005646
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Hyaluronidase in Early Surgery of Nasal Bone Fracture

Abstract: A nasal bone fracture is one of the most common facial injuries and is often treated by closed reduction. Typically, 2 to 3 weeks are needed for patients to return to daily life because the operation is performed after swelling around the fracture site is reduced. This study aimed to investigate that hyaluronidase injection could reduce swelling, perform early operation and return to daily life accelerated. From January 2017 to December 2017, 181 patients with nasal bone fracture were analyzed. 60 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Because nasal bone fractures require surgery after edema is reduced, a considerable amount of time is required between the accident and surgery. Kim et al 18 applied hyaluronidase to reduce edema before nasal bone fracture surgery during a case-control study of 181 patients and showed that when hyaluronidase was applied, a mean of 3 days from trauma to surgery was required and a mean of 8.6 days was required for the control group. Furthermore, a significant reduction in latency due to the edema-reducing effect of hyaluronidase was reported 18 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because nasal bone fractures require surgery after edema is reduced, a considerable amount of time is required between the accident and surgery. Kim et al 18 applied hyaluronidase to reduce edema before nasal bone fracture surgery during a case-control study of 181 patients and showed that when hyaluronidase was applied, a mean of 3 days from trauma to surgery was required and a mean of 8.6 days was required for the control group. Furthermore, a significant reduction in latency due to the edema-reducing effect of hyaluronidase was reported 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al 18 applied hyaluronidase to reduce edema before nasal bone fracture surgery during a case-control study of 181 patients and showed that when hyaluronidase was applied, a mean of 3 days from trauma to surgery was required and a mean of 8.6 days was required for the control group. Furthermore, a significant reduction in latency due to the edema-reducing effect of hyaluronidase was reported 18 . The effect of hyaluronidase on postsurgical edema reduction has been well-demonstrated in animal studies.…”
Section: Discussionmentioning
confidence: 99%
“…Kwoen et al 23 reported that postoperative swelling after GBR with simultaneous dental implant placement was lower in the HUD group, and this result was more effective in the maxilla. In a clinical study of closed reduction surgery after nasal bone fracture, the duration from injury to surgery was significantly lower in the HUD group than the control group, leading to improved patient satisfaction resulting from earlier discharge and return to their daily life 24 . Unlike postoperative swelling, few studies have presented data on postoperative pain related to HUD after oral and maxillofacial surgery.…”
Section: Discussionmentioning
confidence: 96%
“…[3][4][5] Some authors suggest that reduction should be performed 1 to 2 weeks after injury, warranting subsidization of posttraumatic soft tissue edema. 13 In the pediatric population, however, closed reduction is recommended as early as possible due to early bony union after trauma. Because surgeons are more likely to do the surgery with remnant posttraumatic soft tissue edema, it is useful to use a navigation system to aid physicians' ambiguous inspection and palpation.…”
mentioning
confidence: 99%
“…Some authors suggest that reduction should be performed 1 to 2 weeks after injury, warranting subsidization of posttraumatic soft tissue edema 13 . In the pediatric population, however, closed reduction is recommended as early as possible due to early bony union after trauma.…”
mentioning
confidence: 99%